Forbidden option or planned decision? Physically disabled women's narratives on the choice of motherhood. Issue 2 (3rd April 2017) - Lappeteläinen, Anita; Sevón, Eija; Vehkakoski, Tanja
ABSTRACT: This narrative study explores personal narratives by disabled women on their choice to become a mother. Eleven Finnish physically disabled mothers were interviewed. The interview data were analysed using Greimas' actant model. The women produced three types of narratives about their journeys to motherhood: compensation, forbidden option and planned choice. In these narratives, the disabled women struggled with the disabling, oversimplifying and suppressive cultural master narratives of 'good' motherhood. Through the narratives, the women distanced themselves from these dominant cultural narratives and constructed strong agency for themselves as mothers.